Efficiency of entomopathogenic fungi in the control of eggs and larvae of the horn fly Haematobia irritans (Diptera: Muscidae) - Mochi, Dinalva Alves [UNESP]; Monteiro, Antonio Carlos [UNESP]; Ribeiro Machado, Ana Carolina [UNESP]; Yoshida, Luciana [UNESP] (Elsevier B.V., 2010)
The present study assessed the pathogenic effect of isolates E9, IBCB425 and IBCB159 of the Metarhizium anisopliae fungus, JAB06, JAB07 and AM09 of Beauveria bassiana, IBCB133 and CB75 of Isaria fumosorosea (=Paecilomyces fumosoroseus) and CG189 and CG195 of Isaria farinosa (=Paecilomyces farinosus) against eggs and larvae of the horn fly Haematobia irritans. Eggs were inoculated with suspensions containing 10(6), 10(7) and 10(8) conidia ml(-1) of the fungal isolates and observed after 48 h to determine viability. In the larvae study, eggs were allowed to hatch into fresh bovine feces that had been treated with 10(8), 10(7) or 10(6) conidia mg feces(-1). In both studies, 5 days after initial procedures, all formed pupae were transferred to an incubator at 27 +/- 0.5 degrees C until the emergence of the adult flies was complete. The M. anisopliae isolates did not cause the death of H. irritans eggs, but they did promote the death of larvae that hatched from treated eggs, and therefore increased the total mortality. Isolate E9 promoted 100% mortality of treated larvae at a concentration of 10(8) conidia ml(-1). For the B. bassiana isolates, no activity was observed against insect eggs or larvae. Both L fumosorosea isolates promoted significant mortality (p < 0.05) of eggs at every concentration of conidia. Isolate CG195 of L farinosa increased the mortality of larvae and pupae that hatched from treated eggs and promoted significant total mortality (p < 0.05) of the insect at every concentration of conidia. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Metarhizium anisopliae; Beauveria bassiana; Isaria fumosorosea; Isaria farinosa; Horn fly; Biological control